2002
DOI: 10.2166/wst.2002.0278
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the quantity and quality of the microbiological content of sludge in countries with low and high content of pathogens

Abstract: The parasites present in the residual sludge generate by the diverse treatment processes of residual water vary, depending on the socioeconomic and epidemiological conditions of different communities. And although data exist at the global level regarding the microbiological quality of sludge, these data are practically nonexistent in developing countries. Therefore, this project compares the content of the four principal groups of parasites in residual sludge from the United States and Mexico. The marked diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 8 publications
2
14
0
3
Order By: Relevance
“…The concentration of Giardia cysts found in this study (0 to 4800 cysts/g), corroborates what was reported by Hu et al (1996) For oocysts, the number of positive samples identified in this study (8.3 %) was lower than has been reported in previous studies in other countries (Jiménez et al 2002, Lemarchand and Lebaron 2003, Thiriat et al 1997). This may be explained by several factors, including the prevalence of cryptosporidiosis in those communities and the individual characteristics, such as pH, of the sludge matrix studied.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The concentration of Giardia cysts found in this study (0 to 4800 cysts/g), corroborates what was reported by Hu et al (1996) For oocysts, the number of positive samples identified in this study (8.3 %) was lower than has been reported in previous studies in other countries (Jiménez et al 2002, Lemarchand and Lebaron 2003, Thiriat et al 1997). This may be explained by several factors, including the prevalence of cryptosporidiosis in those communities and the individual characteristics, such as pH, of the sludge matrix studied.…”
Section: Discussionsupporting
confidence: 92%
“…Jiménez et al (2002) assessed the viability of Ascaris eggs in sewage sludge samples in Mexico by employing purification technique with steps of washing, filtration, flotation in saturated and centrifugal concentration and then incubated for 20 days at 26°C sulfuric acid (0.05 mol/L). According to the authors, Ascaris eggs were found more frequently when compared to other helminth whereas 90 % of them were viable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, very frequently, Ascaris eggs are common in wastewater and sludge (Cabaret et al, 2001, andJiménez et al, 2002). For this reason, in regulations and very often in research studies, Ascaris is the only helminth considered.…”
Section: Behaviour Of Helminth Ova Per Genusmentioning
confidence: 99%
“…There is not an indicator of this group, but it is generally accepted that they are less resistant than helminth ova to adverse environmental conditions. Table 10.4 Pathogens found in wastewater and sludge (EPA, 1994 andJimenez, 2003 Jiménez et al, 2002. Helminth Ova.-Helminth ova are a special challenge in the field of sludge treatment processes, due to their very high resistance to extreme conditions.…”
Section: Biological Characteristicsmentioning
confidence: 99%